(untitled) (Journal of Science and Technology Research, 2026)
The Bay of Bengal (BoB) is a continuum receiving numerous major rivers including the Mahanadi, Godavari, Krishna, Kaveri, Ganges, Brahmaputra, Meghna, and many more others. The river outputs are greatly impacted by the dynamic circulation system along the shelf. As anticipated, the freshwater influx from rivers leads to lower salinities and shallower mixed layers. Yet, the effect of this extra freshwater input into the bay is unexpectedly complex. Meanwhile, the considerable freshwater flow from these rivers transforms the density and dynamic height of the receiving seas, potentially influencing primary productivity in the northern BoB. Various observational, reanalysis, and satellite datasets—such as river discharge, temperature, salinity, density, and chlorophyll concentration—are analyzed using heterogeneous correlation methods. The data sources include the Copernicus Marine Environment Monitoring Service and ERAInterim. It highlights that Classic estuarine two-layer circulation during monsoonal period is one of the significant consequences of river plume influence on continental shelf. Coriolis force, which is governed by earth rotation, monsoonal effect and buoyant river plumes are what makes this discovery so significant. This study indicates that the highest variability in Sea Surface Salinity (SSS) is found near the mouths of the major rivers, such as the Ganges-Brahmaputra-Meghna (GBM) in the northern BoB and the Irrawaddy in the northern Andaman Sea. There’s also notable variation along the western boundary of the basin, though to a lesser extent. The results show a large increase in surface salinity along the Bangladeshi coast especially in the eastern part in near future, which may affect the area of fresh water plume-suggesting that variations in river flow can significantly influence the dynamic marine ecosystems of the northern BoB during the time period between 2016 and 2020. These modifications are anticipated to cause considerable alterations in the coastal aquatic ecosystems in coastal areas. J. of Sci. and Tech. Res. 6(2): 65-75, 2025